BUILDING SUSTAINABLE TENANCIES: TENANTS’ PREFERENCE CRITERIA IN CHOOSING THE LOCATION OF PURPOSE-BUILT OFFICE BUILDINGS - Ahmad@Baharum, Zarita (International Journal of Property Sciences (E-ISSN: 2229-8568), 2023)
Building sustainable tenancies is a comprehensive strategy used with tenants to establish sustainable relationship connections. Tenants are said to be the lifeblood of the building, thus retaining them is a difficult task that requires a variety of tactics in guaranteeing that they receive high-quality services. According to their business nature & requirements, as well as other considerations that the company may need to take into account, tenants have preferences for location and space. This paper attempts to determine the criteria that tenants consider when choosing a location and space for purpose-built office buildings. Through the use of a quantitative approach, a survey among the tenants of office buildings in Kuala Lumpur was conducted. From the responses gathered, it is found that the Criteria that have the biggest impact on where tenants choose to rent include the property’s condition, type of finishes, cleanliness, competent management and maintenance team, and proximity to transportation in addition, the choices of tenants can also be influenced by criteria such as availability of facilities, location, property condition, security and access control, and branding/image.